Imaging exciton–polariton transport in MoSe2 waveguides - Hu, F.; Luan, Y.; Scott, M. E.; Yan, J.; Mandrus, D. G.; Xu, X.; Fei, Z. (Nature photonics, 2017)
Imaging reveals properties of exciton–polaritons in MoSe 2 waveguides. The exciton–polariton (EP), a half-light and half-matter quasiparticle, is potentially an important element for future photonic and quantum technologies 1 , 2 , 3 , 4 . It provides both strong light–matter interactions and long-distance propagation that is necessary for applications associated with energy or information transfer. Recently, strongly coupled cavity EPs at room temperature have been demonstrated in van der Waals (vdW) materials due to their strongly bound excitons 5 , 6 , 7 , 8 , 9 . Here, we report a nano-optical imaging study of waveguide EPs in MoSe 2 , a prototypical vdW semiconductor. The measured propagation length of the EPs is sensitive to the excitation photon energy and reaches over 12 µm. The polariton wavelength can be conveniently altered from 600 nm down to 300 nm by controlling the waveguide thickness. Furthermore, we found an intriguing back-bending polariton dispersion close to the exciton resonance. The observed EPs in vdW semiconductors could be useful in future nanophotonic circuits operating in the near-infrared to visible spectral regions.